2017
DOI: 10.1007/978-3-319-58469-0_18
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of Emojis in Mobile Authentication

Abstract: Mobile authentication methods protect smartphones from unauthorized access, but also require users to remember and frequently enter PINs, passwords, or graphical patterns. We propose the EmojiAuth scheme with which we study the effects of Emoji use on the usability and user experience of mobile authentication. We conducted two between-subjects studies (lab study: n=53; field study: n=41) comparing EmojiAuth to standard PIN entry. We find that Emo-jiAuth provides good memorability for short passwords and reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…Markov models have proven a useful tool to model userchosen authentication secrets in the past, both for passwords [21], [17], [11] and Android Unlock patterns [30]. We expect them to provide reasonable predictions for the studied EmojiAuth scheme as well, specifically in the light of previous work by Kraus et al [15] which found that common (self-reported) strategies for selecting passcodes were based on creating a story, repeating events of my life, and visual patterns "A-B-A-B". (Note that other common strategies did not necessarily involve a specific order of emoji, such as important things of their lives or tried to select a random passcode, and are thus less well modeled by Markov models.…”
Section: B Introduction To Markov Modelsmentioning
confidence: 68%
See 4 more Smart Citations
“…Markov models have proven a useful tool to model userchosen authentication secrets in the past, both for passwords [21], [17], [11] and Android Unlock patterns [30]. We expect them to provide reasonable predictions for the studied EmojiAuth scheme as well, specifically in the light of previous work by Kraus et al [15] which found that common (self-reported) strategies for selecting passcodes were based on creating a story, repeating events of my life, and visual patterns "A-B-A-B". (Note that other common strategies did not necessarily involve a specific order of emoji, such as important things of their lives or tried to select a random passcode, and are thus less well modeled by Markov models.…”
Section: B Introduction To Markov Modelsmentioning
confidence: 68%
“…In this study, we concentrated on the security of the EmojiAuth scheme, as previous work found that EmojiAuth (with 12 emoji) "provides login times comparable to PIN and reasonable memorability" [15]. We found that the security is substantially higher than for similar systems, specifically Android's graphical authentication scheme [30] and user-chosen 4-digit PINs [6].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations